Disparities in Stroke Patient-Reported Outcomes Measurement Between Healthcare Systems in Brazil - Martins, Sheila Cristina Ouriques; Borelli, Wyllians Vendramini; Secchi, Thais Leite; Mantovani, Gabriel Paulo; Pille, Arthur; Mora Cuervo, Daissy Liliana; Carbonera, Leonardo Augusto; Souza, Ana Claudia de; Martins, Magda Carla Ouriques; Brondani, Rosane; Almeida, Andrea Garcia de; Dal Pizzol, Angélica; et al. (Frontiers in Neurology, 2022)
Introduction Acute stroke interventions, such as stroke units and reperfusion therapy, have the potential to improve outcomes. However, there are many disparities in patient characteristics and access to the best stroke care. Thus, we aim to compare patient-reported outcome measures (PROMs) after stroke in two stroke centers representing the public and private healthcare systems in Brazil. Methods PROMs through the International Consortium for Health Outcomes Measures (ICHOM) were assessed at 90 days after the stroke to compare two Brazilian hospitals in southern Brazil: a public university and a private stroke center, both with stroke protocols and stroke units. Results When compared with the private setting (n = 165), patients from the public hospital (n = 175) were younger, had poorer control of risk factors, had more frequent previous strokes, and arrived with more severe strokes. Both hospitals had a similar percentage of IV thrombolysis treatment. Only 5 patients received mechanical thrombectomy (MT), all in the private hospital. Public hospital patients presented significantly worse outcomes at 3 months, including worse quality of life and functional dependence (60 vs. 48%, p = 0.03). Poor outcome, as measured by the mRS score, was significantly associated with older age, higher NIHSS score, and the presence of heart failure. However, the public practice was a strong predictor of any self-reported disability. Conclusion Patients assisted at a good quality public stroke center with the same protocol used in the private hospital presented worse disability as measured by mRS and patient-reported outcome measures, with greater inability to communicate, dress, toilet, feed, and walk.